Peremajaan Lahan Terdampak Tsunami Menjadi Ruang Terbuka Hijau Melalui Pendekatan Perencanaan Kolaboratif di Kota Banda Aceh (Studi Kasus Hutan Kota BNI Tibang dan Taman Kota BNI Trembesi) - Hafi Munirwan; Marsista Buana Putri; Fran Sinatra (Universitas Batanghari Jambi, 2020)
Green space is an important component of city life that functions to maintain urban ecosystem. The presence of green space is increasingly pressed dueto the rapid rate of urbanization in Indonesia which has an impact on the increasing challenge of green space provisioning in urban area. One of the land that can be optimized as green space is degraded or abandoned landthat can be caused by various factors, one of which is natural disasters. BNI Tibang City Forest and BNI Trembesi City Park are green open space developed on abandoned land affected by the Tsunami disaster that struck Aceh in 2004. This study aims to examine the collaboration between government and non-government stakeholders in regenerating Tsunami affected land into green space area, consisting of BNI Tibang City Forest and BNI City Park. The result of the study showed that the regeneration of abandoned land into green space area in two study cases area has contributed respectively 6.75 hectares and 2.59 hectares. Besides, the study showed that a number of non-governmental stakeholders consisting of non-governmental organizations (NGOs), the private sector, and the community were involved in the initiation, implementation and maintenance stages of the BNI Tibang City Forest and the BNI Trembesi City Park with the collaboration degree reaching the partnership between government and non-government stakeholders.